Encouraging Realistic Expectations in STEM Students: Paradoxical Effects of a Motivational Intervention - Hall, Nathan C.; Sverdlik, Anna (Frontiers in Psychology, 2016)
College students in STEM disciplines are increasingly faced with highly competitive and demanding degree programs and are at risk of academic overconfidence. Following from theory and research highlighting the psychological and developmental risks of unrealistic expectations, the present exploratory study evaluated the longitudinal effects of a motivational intervention encouraging college students in STEM degree programs (N = 52) to consider the importance of downgrading one’s expectations in response to academic setbacks. Contrary to study hypotheses, the results showed intervention participants to report significantly higher expectations and optimism on post-test measures administered four months later, no significant gains in emotional well-being or achievement goal orientations, and lower GPAs over five subsequent semesters. These paradoxical effects underscore the need for additional larger-scale research on the nature of students’ responses to potentially ego-threatening motivational programs in STEM disciplines so as to minimize achievement deficits at the expense of preserving motivational resources.